STUDI KELAYAKAN ATAS POTENSI ZAKAT PERTANIAN DI KECAMATAN TAPALANG KABUPATEN MAMUJU (ANALISIS INDEKS DESA ZAKAT) - Muhammad Anwar; Qadir Gassing; Supardin Supardin (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
Abstract The purpose of this research is to find out how the Potential of Agricultural Zakat in Kec. Tapalang, Kab. Mamuju and to find out how the Kec. Indexation Analysis. Tapalang Based on Zakat Village Index (IDZ). This research is a mixed method research dominated by descriptive-qualitative research. Research location in Baznas Kab. Mamuju and kec. Tapalang. Data obtained from interviews, documents and field observations. The data analysis method, namely primary data and secondary data, is analyzed qualitatively, namely a method of research conducted to seek qualitative truth. The conclusion of this study is that the potential for agricultural zakat in Mamuju Regency in general according to BAZNAS can reach Rp. 37.23 billion. As for the Tapalang sub-district, the zakat potential reaches Rp. 566,719,020 but the unaccounted value of potential agricultural zakat is around 3,312.94 tons for various commodities. This is because the IPPZ (Zakat Potential Mapping Indicator) has not been implemented in Tapalang sub-district for the agricultural sector. So that BAZNAS always socializes the importance of zakat to official government institutions so that the potential can be read and absorbed accurately. Based on the analysis according to the dimensions in the IDZ, the Tapalang sub-district is in the range of 0.41-0.60, which means it is quite good and can be interpreted that these areas may be considered for assistance. Even so, there are dimensions that fall into the unfavorable category, which means they are prioritized for assistance, namely the economic, educational and social dimensions of humanity. Keywords: agricultural zakat, zakat village index